Penilaian Efektivitas Asuransi Kecelakaan Kerja BPJS Ketenagakerjaan Cabang Tanjung Morawa - Layla Rahma Dani; Fauzi Arif Lubis (Universitas Muhammadiyah Surabaya, 2023)
AbstractIn Indonesia, everyone has the right to the effectiveness of work accident insurance to be able to meet the basic needs of a decent life and increase their dignity towards the realization of a prosperous, just and prosperous Indonesian society. In order to create a basis for improving the welfare and protection of workers, the law regulates the implementation of the Social Security Administering Body (BPJS) as a manifestation of social responsibility. The results of this study are: 1) The implementation of the effectiveness of BPJS Employment accident insurance in Tanjung Morawa is very much needed by workers/laborers; 2) Legal protection for the effectiveness of work accident insurance in Tanjung Morawa, has not been implemented as it should be, there are still many workers/laborers who have not been registered as participants in the effectiveness of work accident insurance, due to lack of awareness and not accepting employers in implementing the effectiveness of work accident insurance programs; 3) The effectiveness of work accident insurance in the protection of labor law in Tanjung Morawa through Employment BPJS as an accident insurance provider has fulfilled the elements of work accident insurance protection, but in practice there are still obstacles both in relation to existing regulations or rules and their realization and there are still many complaints about the services and benefits provided by Employment BPJS.Keywords: Employment BPJS, Law, Labor.